2016
DOI: 10.18632/oncotarget.7938
|View full text |Cite
|
Sign up to set email alerts
|

N52 monodeamidated Bcl-xL shows impaired oncogenic propertiesin vivoandin vitro

Abstract: Bcl-xL is a member of the Bcl-2 family, playing a critical role in the survival of tumor cells. Here, we show that Bcl-xL oncogenic function can be uncoupled from its anti-apoptotic activity when it is regulated by the post-translational deamidation of its Asn52.Bcl-xL activity can be regulated by post-translational modifications: deamidation of Asn52 and 66 into Asp residues was reported to occur exclusively in response to DNA damage, and to cripple its anti-apoptotic activity. Our work reports for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 37 publications
(56 reference statements)
2
21
0
Order By: Relevance
“…In addition, one single Asn→Ala substitution generated a shift in the migration distance (compare lanes “AD” and “N66D”, and compare lanes “N52D” and “DA” on gels c, d, and e in Figure 1). The fine separation of proteins granted by these new gel compositions can indeed be used to accurately pinpoint that the modified form (labeled * in WT lanes of Figure 1) above unmodified Bcl-x L co-migrates exactly with the single mutant Bcl-x L N52D, thus confirming what we previously reported with long tris–glycine PAGE [7]. However, these gels still show a difference in the migration distances of Bcl-x L AD and Bcl-x L DA (as 25 cm-long tris–glycine SDS-PAGE already did) even though both proteins have the exact same molecular weight.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…In addition, one single Asn→Ala substitution generated a shift in the migration distance (compare lanes “AD” and “N66D”, and compare lanes “N52D” and “DA” on gels c, d, and e in Figure 1). The fine separation of proteins granted by these new gel compositions can indeed be used to accurately pinpoint that the modified form (labeled * in WT lanes of Figure 1) above unmodified Bcl-x L co-migrates exactly with the single mutant Bcl-x L N52D, thus confirming what we previously reported with long tris–glycine PAGE [7]. However, these gels still show a difference in the migration distances of Bcl-x L AD and Bcl-x L DA (as 25 cm-long tris–glycine SDS-PAGE already did) even though both proteins have the exact same molecular weight.…”
Section: Resultssupporting
confidence: 84%
“…Finally, in a previous study asking whether Bcl-x L could accumulate both deamidation and phosphorylation, we had provided compelling evidence that monodeamidated Bcl-x L could be phosphorylated in response to microtubule inhibition. However, we and others had failed to determine whether doubly-deamidated Bcl-x L could be phosphorylated because of insufficient electrophoretic resolution provided by tris–glycine PAGE [7,8]. We show here that taurine–glycine gels proved efficient to overcome this limitation and found that doubly-deamidated Bcl-x L is eligible for regulation by phosphorylation.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Bcl-XL appears as a double band because of deamidation of two amino acids Asn 52 and Asn 65 into Asp. Thus, the most upper band represents the double deamidated form, which is the only form that is functionally characterized [25]. In mesangial from wildtype mice (Wt), hSK2-ctrl mice (expressing no Cre recombinase, -Cre), and hSK2-tg mice (hSK2tg, expressing Cre recombinase, +Cre), were separated by SDS-PAGE and subjected to Western blot analysis using antibodies against human SK-2 (hSK2, upper panels), mSK-2 (middle panels) and GAPDH (lower panels).…”
Section: Resultsmentioning
confidence: 99%